2010
DOI: 10.1021/ac102114z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Multivalent Ligand Presentation on Gold Glyconanoparticles and the Impact on Lectin Binding

Abstract: Glyconanomaterials, nanomaterials carrying multiple carbohydrate ligands, provide an excellent platform for sensitive protein recognition. Using nanomaterials as the scaffold, multivalent interactions between glycan ligands and proteins have been demonstrated. However, the quantitative analysis of the binding affinity of these glyconanomaterials has been lacking. In this article, we report a new method to measure the binding affinity of glyconanoparticle (GNP)-protein interactions based on a fluorescent compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
135
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 52 publications
8
135
0
Order By: Relevance
“…81 a) b) Wang et al found that the sensitivity of mannose-functionalised nanoparticles towards ConA increased with the spacer length. 82 The authors prepared the glyconanoparticles using a photocoupling method, as previously described in this review, 66 and more flexible spacer linkage exhibited the lowest limit of detection. 82 While these results appear to contradict previous work, 52,76,78 it is possible that the flexibility of the anchor chain is an additional important feature for the targeting and sensitive detection of proteins with glyconanoparticles.…”
Section: Length Of the Anchor Chain That Tethers The Carbohydrate To mentioning
confidence: 99%
“…81 a) b) Wang et al found that the sensitivity of mannose-functionalised nanoparticles towards ConA increased with the spacer length. 82 The authors prepared the glyconanoparticles using a photocoupling method, as previously described in this review, 66 and more flexible spacer linkage exhibited the lowest limit of detection. 82 While these results appear to contradict previous work, 52,76,78 it is possible that the flexibility of the anchor chain is an additional important feature for the targeting and sensitive detection of proteins with glyconanoparticles.…”
Section: Length Of the Anchor Chain That Tethers The Carbohydrate To mentioning
confidence: 99%
“…[35] Therefore, the lectin can act as a crosslinker. Antibodies on the surface captured the A chain(s) of RCA 120 , and the remaining two Lac-binding B chains and RCA 120 in solution aggregated simultaneously GOAL assay [c] 5-AuNP 6-AuNP 7-AuNP RCA 120 Con A WGA 300 (7 nm) [17] 430 (6.2 nm) [23] 500 (1.5 nm) [45] 3 (6.6 nm) [24] 16 (15 nm) [24] 12…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high dielectric constant of AuNPs and electromagnetic coupling between AuNPs and the metal film on the surface, the sensitivity of the surface plasmon resonance (SPR)-based sensor can be increased. Several different materials are also used to support AuNPs such as optical fibres, ITO glass, sol-gel matrix for the detection of human IgG [50], streptavidin [51], interleukin-1β [52] and propanethiol [53]. Similarly, waveguide-mode sensor, which mimic the principle of SPR, has been generated with higher sensitive sensing using AuNP conjugation for the detection of influenza viruses [10][11][12].…”
Section: Aunp-facilitated Label-free Sensorsmentioning
confidence: 99%